Barriers to oral cancer screening: a focus group study of rural Black American adults. Issue 6 (27th August 2012) - Howell, Jennifer L.; Shepperd, James A.; Logan, Henrietta
Abstract Objective Mortality from mouth and throat cancer (MTC) is higher among Black Americans than White Americans partially because of late stage detection through screening. The disparity in mortality is particularly problematic among Black Americans living in rural areas who have limited access to preventative resources. Our study explored barriers to screening for MTC among Black Americans. Methods We conducted nine focus groups among rural Black Americans age 40 years and older (N = 80). Results Content coding of the transcripts of the focus groups revealed three primary barriers to screening. Lack of knowledge (e.g., not knowing about MTC and not knowing MTC symptoms) accounted for 31.8% of all barriers mentioned, lack of resources (e.g., lack of money and health insurance) accounted for 25.0% of all barriers mentioned, and fear (e.g., fear of screening and diagnosis) accounted for 22.9% of all barriers mentioned. Conclusions We placed these barriers within the Theory of Planned Behavior and conclude that interventions aimed at increasing MTC screening among rural Black Americans should first focus on changing people's attitudes about screening by increasing knowledge about MTC and reducing fear. Copyright © 2012 John Wiley & Sons, Ltd.